The Southern Literary Messenger, Vol. I., No. 4, December, 1834 - Various; Heath, James E. (Salt Lake City, UT : Project Gutenberg, 2016)
"The Southern Literary Messenger, Vol. I., No. 4, December, 1834" is a periodical publication that features various writings including essays, articles on literature, and accounts from history, created in the early 19th century. This particular issue contains a historical examination of Tripoli and the Barbary States, detailing its past under Turkish rule and the interactions of its leaders with European powers. The article highlights the shift in governance and the complex relationships between local rulers, the Ottoman Sultan, and European nations during a time of political intrigue and shifting alliances. At the start of the issue, the reader is introduced to the history of Tripoli, specifically focusing on its conquest in 1551 and subsequent governance under the Turkish Empire. It recounts the rise of Hamet, a key figure who ultimately revolted against the Sultan's authority, detailing his pact-making with European nations and the strategic importance of Tripoli in maritime trade and piracy. As the segment unfolds, there are vivid descriptions of conflicts, political maneuvers, and the personal dynamics of power within the government, as well as the harrowing consequences of tyranny that led to Hamet's tragic demise. The narrative blends historical analysis with storytelling, setting the stage for a deeper exploration of the historical and geopolitical themes prevalent in this transformative period. (This is an automatically generated summary.)
Release date is 2016-12-17
Produced by Ron Swanson
Keywords: American literature -- 19th century -- Periodicals